Pengembangan Buku Ajar IPS Terpadu Berbasis 3 Dimensi di SMPN 3 Pasiran - Lumajang dengan Pendekatan Kontekstual Learning - Triwilujeng Ayuningtyas; Fidyah Jayatri; Rohmayanti Rohmayanti (Proceedings of The ICECRS, 2019)
The involvement of teaching materials for the ongoing teaching and learning activities in schools is very important, especially teaching materials that have appeal and are arranged creatively for use by students. This attraction will encourage students to be more enthusiastic about learning. The motivations of students are inseparable from the role of educators in choosing teaching materials that are appropriate to the needs of their students. Educators also need to develop self-creativity to be able to create creative teaching materials. Teaching materials in the form of teaching books are generally in the form of textbooks and student worksheets so that the tendency of students to be lazy and bored in learning appears. Therefore we need teaching materials that have more appeal so students can easily understand. One of the creative teaching materials that can be developed is a three-dimensional textbook that can be used for students entering the age of children to adolescents. This textbook is intended to motivate students to be more active in reading so that they are able to link the examples presented in the book into real conditions in the surrounding environment.